The Urgency of Pre-Marital Guidance on Catin (Bride-To-Be) Through an Abstinence Approach in Cirebon City - Karmila, Wati; Parid, Diana (Sosial Budaya, 2024)
This study aims to reveal in depth the urgency of premarital guidance on catin (bride-to-be) through the abstinence approach in the city of Cirebon. The approach in this research uses a qualitative with the type of case study with analytical descriptive methods. The data collection techniques used in this study: observation, interviews, and documentation studies. While analyzing the data by using: Data Reduction, data display, and data conclusion. While. The results showed that 1) The KUA Program provides a schedule for the implementation of Production Health Counseling, STIs, and HIV-AIDS activities as well as advice and Health Examinations for Brides-to-be together with LKB Puskemas Officers to carry out pre-test counseling and examination of STIs and HIV-AIDS 2) The process of implementing premarital guidance on catin (bride-to-be) in Cirebon City is carried out through various strategies through an abstinence approach 3) The duration of delivery of counseling materials is very short.  there are still brides who are not present, the percentage between the number of brides is still not 100%, 4) The result is a lot of knowledge that can improve the quality of marriage and create a happy and prosperous family, and avoid HIV Aids